1979
DOI: 10.1128/aem.37.4.779-781.1979
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide-Entrapped Rhizobium as an Inoculant for Legumes

Abstract: Pot experiments showed that Rhizobium japonicum cells entrapped in a polyacrylamide gel could be used as an inoculant for soybeans and compared favorably to laboratory-made peat base inoculant containing the same bacterial strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 2 publications
2
26
0
Order By: Relevance
“…In addition, the viability of most organisms tested hitherto decreased appreciably with storage time. On the other hand, studies with entrapped Rhizobium in various nonsterile polymer gels by nonsterile procedures (9,14) showed that the entrapping process did not significantly decrease either the number of bacteria or their viability as shown in the present study and in the work of Fravel et al (11).…”
Section: -77a 1985)supporting
confidence: 64%
See 1 more Smart Citation
“…In addition, the viability of most organisms tested hitherto decreased appreciably with storage time. On the other hand, studies with entrapped Rhizobium in various nonsterile polymer gels by nonsterile procedures (9,14) showed that the entrapping process did not significantly decrease either the number of bacteria or their viability as shown in the present study and in the work of Fravel et al (11).…”
Section: -77a 1985)supporting
confidence: 64%
“…Release of the immobilized living material was considered a disadvantage of the system (4,5,7,8,12,13,16,20,21,26). A few reports suggested the use of several polymer gels for entrapping fungi and bacteria for use as agricultural inoculants (9,11,14,19).…”
mentioning
confidence: 99%
“…These gel-based inoculants compared favourably with a peat-based inoculant. Drying these inoculants prevents the multiplication of contaminants, renders inoculants more easy to handle in the field but lowers the final concentration of rhizobia, and in the case of polyacrylamide decreases the effectiveness of rhizobia (Dommergues et al 1979).…”
Section: Introductionmentioning
confidence: 99%
“…is important efficiency character being taken into consideration while formulating the biofertilizers. (Kloepper and Schroth, 1981), compost, coconut shell powder, peat (Temprano et al 2002), talc (Dommergues et al 1979), perlite (Bashan,1986), zeolite, vermiculite, perlite, rice bran, wheat bran, polyacrylamide (Cassidy et al 1996), charcoal, sawdust, organic manure are used for production of biofertilizers. These carriers provide support to the microbial culture and help in the survival capacity of microorganism.…”
Section: Types Of Bioformulations Availablementioning
confidence: 99%